2009
DOI: 10.2337/db09-0530
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Metabolically Active Brown Adipose Tissue in Healthy Adult Humans

Abstract: OBJECTIVEThe significant roles of brown adipose tissue (BAT) in the regulation of energy expenditure and adiposity are established in small rodents but have been controversial in humans. The objective is to examine the prevalence of metabolically active BAT in healthy adult humans and to clarify the effects of cold exposure and adiposity.RESEARCH DESIGN AND METHODSIn vivo 2-[18F]fluoro-2-deoxyglucose (FDG) uptake into adipose tissue was measured in 56 healthy volunteers (31 male and 25 female subjects) aged 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
1,547
8
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,700 publications
(1,684 citation statements)
references
References 24 publications
82
1,547
8
14
Order By: Relevance
“…The amount of BAT in humans has been shown to vary with age, BMI, and gender, compounding the complexity of these studies. [11][12][13] Beige adipocytes are found interspersed within the WAT, [14][15][16] specifically the subcutaneous WAT (scWAT), in response to various stimuli including cold exposure and b-adrenergic stimulation. Beige cells come from a Myf5-lineage distinguishing them from BAT, but can, upon stimulation, express high levels of UCP1 and contribute to non-shivering thermogenesis.…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The amount of BAT in humans has been shown to vary with age, BMI, and gender, compounding the complexity of these studies. [11][12][13] Beige adipocytes are found interspersed within the WAT, [14][15][16] specifically the subcutaneous WAT (scWAT), in response to various stimuli including cold exposure and b-adrenergic stimulation. Beige cells come from a Myf5-lineage distinguishing them from BAT, but can, upon stimulation, express high levels of UCP1 and contribute to non-shivering thermogenesis.…”
Section: Adipose Tissuementioning
confidence: 99%
“…76 It is possible that the type of exercise, the ambient temperature in which the exercise occurs, the pre-training BMI, and the initial cardiorespiratory fitness levels of the subjects may all be important factors in determining if exercise training in humans induces a beiging of WAT. Another potential explanation is that similar to the variable effects of cold on BAT activity in humans, 11,13 some individuals may have a greater genetic propensity to increase beiging of scWAT in response to exercise training. Additional studies are needed to fully understand if beiging of scWAT is an important physiological response to exercise in human subjects, and in subjects that demonstrate beiging of scWAT, if there are metabolic consequences to this adaptation.…”
Section: Does Exercise Cause Beiging Of Wat In Humans?mentioning
confidence: 99%
“…1 Obesity is defined by the expansion of white adipose tissue (WAT), but recent evidence suggests that the adult human body also contains functionally distinct, brown adipose tissue. [2][3][4][5][6][7][8] In contrast to WAT, which has a primary role in energy storage, brown adipose tissue specializes in energy dissipation as heat (Cannon and Nedergaard 9 ). This thermogenic property of brown fat results from its high content of mitochondria, cell organelles where energy dissipation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Three manuscripts published in the same issue of the New England Journal of Medicine, from the USA (Cypess et al 2009), Finland (Virtanen et al 2009), and the Netherlands (van Marken Lichtenbelt et al 2009), and followed shortly by a manuscript from Japan (Saito et al 2009), clearly indicated that BAT was present in a significant number of adults and that its presence and activity (measured by proxy as 18 F FDG uptake by PET scanning) correlated with indices of healthy metabolism. Conversely, obesity, diabetes and age inversely correlated with BAT activity (Pfannenberg et al 2010).…”
Section: Implications Of the Rediscovery Of Bat In Adult Humansmentioning
confidence: 99%